Assessment of Awareness, Adoption Behavior and Impact of the Crop Insurance Scheme (PMFBY) in Kangra District of Himachal Pradesh - Kumari Sandeep; Amit; Shilpa (Annals of Arid Zone, 2025)
Agriculture inherently involves numerous risks that directly affect farmer’s livelihood. To mitigate these risks, crop insurance serves as a vital institutional mechanism. Recognizing its importance in risk management, this paper aimed to assess impact of Pradhan Mantri Fasal Bima Yojana on farmer’s livelihood status. Subsequently, the paper aimed to evaluate the level of awareness and identify the factors influencing farmers' decisions to purchase crop insurance. The primary data was collected from 120 farmers consisting of 60 beneficiaries and 60 non-beneficiaries by using simple random sampling technique in the Kangra district of Himachal Pradesh. The selected beneficiaries were further divided into two groups i.e. claim holders and non-claim holders. Livelihood framework analysis showed that beneficiaries had a better position in social, financial and human assets status than non-beneficiaries. The study revealed a significantly lower level of awareness regarding the scheme among non-beneficiaries compared to beneficiaries. Additionally, landholding size, income level, awareness regarding scheme and contact with extension agents emerged as key factors which influenced the adoption of PMFBY. Based on the findings it is recommended that policymakers and stakeholders should focus on enhancing awareness and outreach efforts regarding crop insurance, particularly targeting farmers with smaller landholdings and lower incomes. Additionally, strengthening the engagement of extension agents can play a crucial role in promoting the adoption of PMFBY, consequently uplifting the overall livelihood status of farmers.